2016
DOI: 10.3390/jof2010006
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Pathogenic Fungi Reveals Highly Expressed Conserved Cell Wall Proteins

Abstract: We are presenting a quantitative proteomics tally of the most commonly expressed conserved fungal proteins of the cytosol, the cell wall, and the secretome. It was our goal to identify fungi-typical proteins that do not share significant homology with human proteins. Such fungal proteins are of interest to the development of vaccines or drug targets. Protein samples were derived from 13 fungal species, cultured in rich or in minimal media; these included clinical isolates of Aspergillus, Candida, Mucor, Crypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 89 publications
2
35
1
Order By: Relevance
“…Querying for proteins that are enriched in the EV fraction compared to the whole cell lysate, as has been done for EVs from different cancer cell types, is needed for the identification of EV biomarkers and proteins that define the function of fungal EVs. This is done with fungal cell wall proteomics which generally employs a comparison with whole cell lysate to minimize the influence of proteins that are highly abundant in the cell and ubiquitous in proteomic analyses . Recent studies on M. sympodialis and C. albicans have compared the protein composition of EVs to whole cell lysate and biofilm matrix respectively.…”
Section: Comparison Of Proteomic Profiles Of Evs From Different Fungamentioning
confidence: 99%
“…Querying for proteins that are enriched in the EV fraction compared to the whole cell lysate, as has been done for EVs from different cancer cell types, is needed for the identification of EV biomarkers and proteins that define the function of fungal EVs. This is done with fungal cell wall proteomics which generally employs a comparison with whole cell lysate to minimize the influence of proteins that are highly abundant in the cell and ubiquitous in proteomic analyses . Recent studies on M. sympodialis and C. albicans have compared the protein composition of EVs to whole cell lysate and biofilm matrix respectively.…”
Section: Comparison Of Proteomic Profiles Of Evs From Different Fungamentioning
confidence: 99%
“…The JF5 antigen implies that cell wall proteins may represent a particularly interesting subset of the whole proteome. Champer et al [104] identified highly expressed cell wall proteins that are conserved in different fungal pathogens and some of them showing only limited sequence conservation may be suitable for specific diagnosis of IA.…”
Section: Detection Of Antigensmentioning
confidence: 99%
“…It has been suggested that the cell wall proteins of A. fumigatus having no homology with humans, but showing homology with other fungal proteins, can be considered as ideal vaccine candidates against fungal pathogens. 40 Recently, Tiwari et al found the Asp fl 2 allergenic protein at germinating stage of Aspergillus flavus and showed no homology with human proteome. 41 Previously, Gautam et al have also reported Asp f2 and Asp f13 using the immunoproteomic approach and showed antibodies against these proteins in the serum samples of ABPA patients.…”
Section: Resultsmentioning
confidence: 99%